2016
DOI: 10.1007/s12640-016-9668-7
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Administration of S-Adenosylhomocysteine or S-Adenosylmethionine Attenuates the Increases in the Cortical Extracellular Levels of Dimethylarginines Without Affecting cGMP Level in Rats with Acute Liver Failure

Abstract: Alterations in brain nitric oxide (NO)/cGMP synthesis contribute to the pathogenesis of hepatic encephalopathy (HE). An increased asymmetrically dimethylated derivative of l-arginine (ADMA), an endogenous inhibitor of NO synthases, was observed in plasma of HE patients and animal models. It is not clear whether changes in brain ADMA reflect its increased local synthesis therefore affecting NO/cGMP pathway, or are a consequence of its increased peripheral blood content. We measured extracellular concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…A significant impact of ADMA on CBF regulation under resting and pathologically changed conditions by NOS inhibition has been previously indicated (Iadecola 1993). Previously, we demonstrated that TAA administration resulted in a significant increase in the ADMA concentration in microdialysates of the prefrontal cortex, brain tissue homogenate and peripheral blood Czarnecka et al 2017b). Concentration of ADMA is higher in cerebellum and blood vessels than in other regions of the brain (Ueno et al 1992), what may explain why in TAA rats L-arginine led to dilation of the MCAs and improved CBF more effectively in the cerebellum than in the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…A significant impact of ADMA on CBF regulation under resting and pathologically changed conditions by NOS inhibition has been previously indicated (Iadecola 1993). Previously, we demonstrated that TAA administration resulted in a significant increase in the ADMA concentration in microdialysates of the prefrontal cortex, brain tissue homogenate and peripheral blood Czarnecka et al 2017b). Concentration of ADMA is higher in cerebellum and blood vessels than in other regions of the brain (Ueno et al 1992), what may explain why in TAA rats L-arginine led to dilation of the MCAs and improved CBF more effectively in the cerebellum than in the prefrontal cortex.…”
Section: Discussionsupporting
confidence: 55%
“…; Czarnecka et al . ). Concentration of ADMA is higher in cerebellum and blood vessels than in other regions of the brain (Ueno et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Taurine has an antioxidant effect, restores the expression of endothelial NO synthase, which is the main endothelium protective pharmacodynamic effect (Battson et al 2017, Ito et al 2012, Rukan et al 2013. Ademethionine is involved in transmethylation, transsulfurization, and transamination reactions, and by inhibiting the PRMT enzyme and preventing the ADMA formation, leads to an increased expression of the eNOS enzyme (Czarnecka et al 2017, Kim et al 2013, Sukhanov et al 2014, Tang et al 2018).…”
Section: Introductionmentioning
confidence: 99%